PENDAMPINGAN PEMBUKUAN BANK SAMPAH SEBAGAI PENDUKUNG EKONOMI SIRKULAR DI RW 3 KELURAHAN MANGUNHARJO KECAMATAN TEMBALANG KOTA SEMARANG - Ahmad Rudi Yulianto; Hendri Setyawan; Chrisna Suhendi (Universitas Mataram, 2025)
Community-based waste management through the waste bank in RW 3 Mangunharjo Subdistrict faced significant constraints, particularly in its manual, decentralized, and error-prone bookkeeping system, which resulted in low transparency and reduced public trust. Nevertheless, waste banks are practical implementations of the circular economy that transform waste into valuable economic resources. This community service activity aimed to enhance the waste bank's administrative governance to be more orderly, accountable, and sustainable, thereby strengthening its role as a micro-level circular economy enabler. The methodology employed was a participatory approach consisting of four interconnected stages: initial identification and coordination, technical training and assistance (manual and Excel bookkeeping), implementation and monitoring, and evaluation and follow-up, including the drafting of Standard Operating Procedures (SOP). The program's results demonstrate substantial governance improvement through the implementation of an integrated bookkeeping system, combining standardized manual recording (Master Transaction Book and Customer Savings Book) with digitalization based on Microsoft Excel. This improvement increased transparency, accelerated the reporting process, minimized data loss risk, and directly fostered public trust and participation. The increased participation and volume of managed waste led to a rise in the economic value from waste sales, a true reflection of the circular economy cycle. In conclusion, the provision of an efficient and transparent bookkeeping system is the primary prerequisite that was successfully met for the waste bank to effectively function as a key actor in driving circular economy sustainability.